Byzantine war against Christians – an "emphylios polemos"? - STOURAITIS, Ioannis (Byzantina Symmeikta, 2010)
The Byzantine civil wars have been the subject of studies which aimed to analyze and interpret the political and military dimension of the phenomenon of armed conflicts inside the Byzantine society. The ideological aspect of civil war in Byzantium has received less attention. During my study on Byzantine war ideology, I noticed that there are some cases of Byzantine authors of the period after the 9th century that present Byzantine war against another Christian people as a civil one. Beginning with a short overview of the Byzantines’ understanding of the term emphylios polemos which modern researchers interpret usually with the modern term civil war, this study will concentrate on the ideological and political similarities or differences between Byzantine civil war and Byzantine war against Christian enemies.